Production of Ceramic Membrane Based on Acid- and Alkali-Activated Metakaolinite as Cooling Material for Monocrystalline Silicon Solar Cell - Septiani Septiani; Wahyu Febri Ramadhy; Angie Islammiyati; Winda Rahmalia (Syarif Hidayatullah State Islamic University, 2019)
Ceramic membrane based on acid- and alkali-activated metakaolinite has been produced. It was tested as a cooling material for monocrystalline silicon solar cells. Membrane was made by several stages, such as calcination of natural kaolinite at 600 oC for 6 hours to obtain metakaolinite, activation of metakaolinite by concentrated HCl and KOH, and preparation of ceramic membrane. Kaolinite, metakaolinite, and activated metakaolinite were characterized by X-ray diffraction (XRD), X-ray fluorescence (XRF), Fourier Transform Infra-red (FTIR), and gas sorption analyzer (GSA). Diffractogram of XRD showed that there was a structural change between activated metakaolinite and natural kaolinite. XRF analysis indicated that the Si/Al of HCl activated metakaolinite was three times higher than natural kaolinite. Activated metakaolinite was made into membrane by adding a binder, then heated at 800 °C for 6 hours. PV cells with and without cooling material were then analyzed their electrical performances. It was found that the maximum energy conversion yield of PV cells without using cooling material was 2.30%, while the maximum energy conversion yield of PV cells with cooling material of meta-kaolinite activated by HCl and KOH were respectively 2.72% and 2.94%.